Analysis of Oily Dusts Emitted During Metal Surface Treatment in Laboratory Conditions - Hurmamatov A. M.; Boyto’rayev S. B. (International Journal on Orange Technologies, 2023)
In this article, in order to cover the metal surface in the procedure of processing the metal surface, the procedure of processing the metal heated at high temperature with the help of motor oils is studied in laboratory conditions. In order to study this process, a laboratory device was used. Oily gases produced in laboratory conditions were studied. The obtained results were compared with the permitted concentration of gases. Absorption cleaning was recommended in order to retain gases above the permitted norm. The results obtained by the proposed new device were analyzed.